2016
DOI: 10.1002/2016ja022552
|View full text |Cite
|
Sign up to set email alerts
|

MESSENGER observations of cusp plasma filaments at Mercury

Abstract: The MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) spacecraft while in orbit about Mercury observed highly localized, ~3‐s‐long reductions in the dayside magnetospheric magnetic field, with amplitudes up to 90% of the ambient intensity. These magnetic field depressions are termed cusp filaments because they were observed from just poleward of the magnetospheric cusp to midlatitudes, i.e., ~55° to 85°N. We analyzed 345 high‐ and low‐altitude cusp filaments identified from MESSENGER ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 58 publications
2
45
0
Order By: Relevance
“…However, there are limitations to this conclusion. The supporting work only superposed 16 cusp events (Poh et al, ). Although this gives a good presentation of the cusp, the number of events used is not large enough to give a more statistical idea of Mercury's cusp ions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, there are limitations to this conclusion. The supporting work only superposed 16 cusp events (Poh et al, ). Although this gives a good presentation of the cusp, the number of events used is not large enough to give a more statistical idea of Mercury's cusp ions.…”
Section: Discussionmentioning
confidence: 93%
“…If we assume that reconnection at Mercury's dayside magnetopause is occurring near continuously, then this means that most of the particles injected into the cusp are lost to the planet (and do not mirror to form the plasma mantle). Superposed cusp ion observation analysis shows that ions are mainly observed to be flowing toward the planet with pitch angles of 0–90° measured in the northern cusp (Poh et al, ). These observations took place close to the mirror point, so we assume that most of these particles did not mirror and would not be able to form the mantle, supporting our idea that the mantle is not a permanent feature of Mercury's magnetosphere.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, as indicated by the close correspondence between the colors along the trajectory and those in the XZ plane, the spatial variations in the modeled field associated with crossings of key magnetospheric boundaries, including the tail current sheet (as indicated by the polarity reversal of B x ) and the dayside magnetopause (as indicated by the sharp discontinuity in the magnitude of B z ), all match the observations very well. Furthermore, Figure d shows a comparison of the simulated plasma pressure P sim with the observed magnetic field strength | B obs | along the MESSENGER trajectory, from which one can identify the location of the cusp where a field depression is expected due to enhanced plasma density (Poh et al, ; Raines et al, ). It can be seen that the simulated plasma pressure exhibits a localized enhancement (white colors in Figure ) in the northern high‐latitude region, which colocates with the portion of the spacecraft trajectory where strong magnetic field depressions (green and blue colors) were observed.…”
Section: Global Magnetosphere Simulations Of Hcm Eventsmentioning
confidence: 99%
“…Under more typical conditions the spacecraft would have crossed the magnetopause in the~1,200-1,500-km altitude region. Again, for a typical pass this is the region where the spacecraft would be expected to transition from the closed dayside magnetosphere into the northern cusp (e.g., Poh et al, 2016 ;Raines et al, 2014 ;Winslow et al, 2012). At this point the spacecraft entered the high-latitude magnetosphere at an altitude of 410 km and a local time of 13:00.…”
Section: Ddm Magnetosheath Plasma Observationsmentioning
confidence: 99%
“…The newly opened Mercury field lines carried tailward by the solar wind all map to the north or south magnetospheric cusps and pivot about the cusps as the high-altitude end is incorporated into the tail lobes. Detailed analyses by Poh et al (2016) have shown that it is very likely that these filaments are the low-altitude extensions of flux transfer events. Solar wind particles generally have a significant component of their velocity parallel to the interplanetary magnetic field.…”
Section: Introductionmentioning
confidence: 99%